Mass of the Stabilized Radion in the Limit of Finite Quartic Coupling - Ali Tofighi; Vahid Reza Shajiee (Advances in High Energy Physics)
We present an exact treatment of the modulus stabilization condition with the general boundary conditions of the bulk scalar field in the Randall-Sundrum model. We find analytical expressions for the value of the modulus and the mass of the radion.